Analisis Pengaruh Kepemilikan Saham terkonsentrasi, pemerintah dan asing, Terhadap Pengungkapan Tanggungjawab Sosial Perusahaan - Julia .; Erwin Masud (JEM Jurnal Ekonomi dan Manajemen, 2017)
The purpose of this study was to test the effect of ownership structure on the disclosure of corporate social responsibility in the annual report of the Indonesian banking sector in 2013 through 2015 are listed in the Indonesia Stock Exchange (BEI). This research is quantitative using simple random sampling method. The data used in this study secondary data, banking 2013-2015 annual report. Sources of data obtained through the website of the Stock Exchange data using eviews with OLS regression. The results of the study hypothesis for H1, H2, and H3 which influence the structure of ownership (concentrated ownership, government, and foreign) on the disclosure of corporate social responsibility, is accepted.